1992
DOI: 10.1002/1097-0142(19920215)69:4<893::aid-cncr2820690410>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

A chronopharmacologic phase II clinical trial with 5-fluorouracil, folinic acid, and oxaliplatin using an ambulatory multichannel programmable pump. High antitumor effectiveness against metastatic colorectal cancer

Abstract: A significant increase in the dose intensity of chemotherapy with fluoropyrimidines and platinum complexes has resulted from selective circadian timing and/or circadian modulation of the infusion rate. The relevance of such chronopharmacologic strategy for improving the outcome of metastatic colorectal cancer was evaluated in an extended Phase II clinical trial involving 93 patients. Cancer 1992; 69:893–899.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
120
0
4

Year Published

1994
1994
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 312 publications
(124 citation statements)
references
References 22 publications
0
120
0
4
Order By: Relevance
“…When OHP is infused in a chronomodulate setting (as a 12-h infusion) or flat infusion for 5 days, these hypersensitivity reactions do not occur. In particular, 151 patients submitted to 1087 constant rate continuous infusion courses of OHP, and 491 patients submitted to 3106 chronomodulate OHP courses did not experience any hypersensitivity reactions (Caussanel et al, 1990;Levi et al, 1992Levi et al, , 1993Levi et al, , 1994bLevi et al, , 1997Levi et al, , 1999Bertheault-Cvitkovic et al, 1996). Therefore, the incapacity of these schedules to produce hypersensitivity might be due to a long time infusion rather than to failure of activation of the immune system (which presents a circadian rhythm) in a chronomodulate setting (Levi et al, 1994a).…”
Section: Discussionmentioning
confidence: 99%
“…When OHP is infused in a chronomodulate setting (as a 12-h infusion) or flat infusion for 5 days, these hypersensitivity reactions do not occur. In particular, 151 patients submitted to 1087 constant rate continuous infusion courses of OHP, and 491 patients submitted to 3106 chronomodulate OHP courses did not experience any hypersensitivity reactions (Caussanel et al, 1990;Levi et al, 1992Levi et al, , 1993Levi et al, , 1994bLevi et al, , 1997Levi et al, , 1999Bertheault-Cvitkovic et al, 1996). Therefore, the incapacity of these schedules to produce hypersensitivity might be due to a long time infusion rather than to failure of activation of the immune system (which presents a circadian rhythm) in a chronomodulate setting (Levi et al, 1994a).…”
Section: Discussionmentioning
confidence: 99%
“…Oxaliplatin showed additive or synergistic activity when associated to 5-FU, even in 5-FU-resistant cell lines (Becouarn et al, 2001). It has been registered worldwide for the treatment of advanced colorectal cancer, where, in association with 5-FU, it was reported to yield a response rate of 36 -58% (Levi et al, 1992;Levi et al, 1994;De Gramont et al, 2000). In in vitro studies, oxaliplatin was demonstrated to inhibit the growth of several gastric cancer cell lines (Eriguchi et al, 2003).…”
mentioning
confidence: 99%
“…In studies carried out by Levi et al (1992), Bertheault-Cvitkovic et al (1996) and Giacchetti et al (1997), in which 20-30% of patients from various trials were referred for 48-h infusion, and FA (500 mg m-2), given for 2 h on each of the 2 days. All patients had at least one metastasis, and 15 had two or more.…”
Section: Combination Therapy First-line Treatmentmentioning
confidence: 99%
“…Examples of the clinical trials undertaken with oxaliplatin are outlined below (Levi et al, 1992;BertheaultCvitkovic et al, 1996;Bismuth et al, 1996;Machover et al, 1996; Becouarn et al, 1997; Giacchetti et al, 1997 The results of this study are shown in Table 1. A partial response was achieved in 10 of the 37 evaluable patients, giving an overall response rate of 27%, which is in line with the rate expected for 5-FU/leucovorin as first-line treatment.…”
mentioning
confidence: 98%
See 1 more Smart Citation